The determinants of interest rates in the informal financial sector and its effects on microfinance - a case study of the Ashanti Region of Ghana - Banibensu, Elike Mensa (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirement for the degree of Master of Science in Development Policy and Planning.